2006
DOI: 10.5713/ajas.2006.390
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rumen-protected Choline Addition on Milk Performance and Blood Metabolic Parameters in Transition Dairy Cows

Abstract: This work was conducted to study the effect of rumen-protected choline (RPC) addition on milk performance and blood metabolic parameters in transition dairy cows. In Experiment 1, fourteen Chinese Holstein dairy cows were supplemented with 0 or 20 g/d of RPC from 7 d before expected calving to 21 d post partum. Feeding of RPC tended to increase milk yield and milk protein percentage, while milk fat and lactose percentage were not changed. Plasma concentrations of glucose tended to increase as cows consumed RPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 19 publications
3
22
1
9
Order By: Relevance
“…In the present study, differences in mean prepartum DMI were not determined; but postpartum DMI for MET and MIX treatments were significantly higher than for the CON treatment. In accordance with previous reports, rumen-protected choline supplementation did not affect DMI [8,21,22] . As a result of many scientific studies have shown that supplemented with methionine and rumen-protected choline to transition rations in dairy cattle may be caused different DMI.…”
Section: Discussionsupporting
confidence: 80%
“…In the present study, differences in mean prepartum DMI were not determined; but postpartum DMI for MET and MIX treatments were significantly higher than for the CON treatment. In accordance with previous reports, rumen-protected choline supplementation did not affect DMI [8,21,22] . As a result of many scientific studies have shown that supplemented with methionine and rumen-protected choline to transition rations in dairy cattle may be caused different DMI.…”
Section: Discussionsupporting
confidence: 80%
“…7, 2018 (Table 7). Others have reported increased (Janovick Guretzky et al, 2006 in the prepartum period; Elek et al, 2013;Amrutkar et al, 2015), decreased (Mohsen et al, 2011), or no effect (Janovick Guretzky et al, 2006 in the postpartum period; Xu et al, 2006;Ardalan et al, 2011) of RPC ion supplementation on circulating concentrations of TAG in dairy cows. This lack of agreement among laboratories may reflect different sampling times in relation to feeding, fewer samples collected than collected in the current experiment, and different amounts of fat intake.…”
Section: Fat Loadingmentioning
confidence: 99%
“…The feeding of RPC ions (11 to 15 g/d) to pregnant, nonlactating cows in positive EB usually had no effect on plasma concentrations of long-chain fatty acids (Piepenbrink and Overton, 2003; Table 7. Effect of increasing intake of ruminally protected choline (RPC) ions on plasma concentrations of metabolites, insulin, and haptoglobin during the restricted feeding period of pregnant, nonlactating multiparous Holstein cows following a pulse dose intake of fat Measure Plasma was collected at 0, 5, 7, 9, 11, 13, 15, 17, and 19 2003; Janovick Guretzky et al, 2006;Xu et al, 2006;Zahra et al, 2006;Sun et al, 2016). It is unknown why RPC ions consumed in 2 very different amounts (6.5 and 25.8 g/d) would similarly increase plasma concentrations of insulin in cows fed AL amounts of feed.…”
Section: Plasma Metabolites In Al and R Feeding Phasesmentioning
confidence: 99%
“…However, choline's effect on milk yield was attributable mainly to increased milk production (4.4 kg/day) in animals with body condition score ≥4 three weeks before calving, that were also consuming more feed. Supplementation of rumen-protected choline would therefore seem to be essential for optimising high-quality milk production in high-yielding dairy cows, as also reported in subsequent studies (Davidson et al, 2008;Elek et al, 2008;Xu et al, 2006), particularly in animals fed basal diets that limit post-ruminal methionine supply. The magnitude of the production response is likely to be affected by basal diet composition, the dose and mode of administration of the rumen-protected choline, and the stage of lactation, as discussed elsewhere (Baldi & Pinotti, 2006;National Research Council, 2001).…”
Section: Recent Advance In Choline Supplementation In Dairy Cowmentioning
confidence: 83%
“…For example, Pinotti et al (2010) investigated the effects of RPC administration on milk production by a regression model based on the results of 11 different studies (42 experimental groups) published between 1991 and 2008 (Davidson et al, 2008;Deuchler et al, 1998;Elek et al, 2008;Erdman et al, 1991;Hartwell et al, 2000;Janovick Guretzky et al, 2006;Pipenbrink and Overton, 2003;Pinotti et al, 2003;Pinotti et al, 2004;Xu et al, 2006;Zahra et al, 2006). The analysis included RPC supplementation (control/RPC) as fixed effect, the variability among experiments as random effect and their interaction.…”
Section: Systematic Analysis Of Choline Supplementation In Dairy Cowsmentioning
confidence: 99%